Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Find reliable answers to your questions from a wide community of knowledgeable experts on our user-friendly Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To find the values of [tex]\( c \)[/tex] and [tex]\( d \)[/tex] that make the equation
[tex]\[ \sqrt{\frac{50 x^6 y^3}{9 x^8}} = \frac{5 y^6 \sqrt{2 y}}{d x} \][/tex]
true, we will simplify both sides of the equation and compare the expressions.
### Step 1: Simplify the Left Side
The left-hand side of the equation is:
[tex]\[ \sqrt{\frac{50 x^6 y^3}{9 x^8}} \][/tex]
Simplifying the expression inside the square root:
[tex]\[ \frac{50 x^6 y^3}{9 x^8} = \frac{50 y^3}{9 x^2} \][/tex]
Now apply the square root:
[tex]\[ \sqrt{\frac{50 y^3}{9 x^2}} = \frac{\sqrt{50 y^3}}{\sqrt{9 x^2}} \][/tex]
This can be further simplified to:
[tex]\[ \frac{\sqrt{50} \cdot \sqrt{y^3}}{3 x} = \frac{\sqrt{50} \cdot y^{3/2}}{3 x} \][/tex]
### Step 2: Simplify the Right Side
The right-hand side of the equation is:
[tex]\[ \frac{5 y^6 \sqrt{2 y}}{d x} \][/tex]
Simplifying the expression inside the numerator:
[tex]\[ 5 y^6 \sqrt{2 y} = 5 \cdot \sqrt{2} \cdot y^6 \cdot y^{1/2} = 5 \cdot \sqrt{2} \cdot y^{6 + 1/2} = 5 \cdot \sqrt{2} \cdot y^{13/2} \][/tex]
So, the right side becomes:
[tex]\[ \frac{5 \sqrt{2} y^{13/2}}{d x} \][/tex]
### Step 3: Equate the Simplified Forms
Equating the simplified left and right sides:
[tex]\[ \frac{\sqrt{50} \cdot y^{3/2}}{3 x} = \frac{5 \sqrt{2} \cdot y^{13/2}}{d x} \][/tex]
For the equation to be true, the powers of [tex]\( y \)[/tex] and [tex]\( x \)[/tex] must match on both sides, as well as the coefficients:
- The power of [tex]\( y \)[/tex] in [tex]\(\sqrt{50} \cdot y^{3/2}\)[/tex] is [tex]\( 3/2 \)[/tex].
- The power of [tex]\( y \)[/tex] in [tex]\( 5 \sqrt{2} \cdot y^{13/2}\)[/tex] is [tex]\( 13/2 \)[/tex].
This implies:
[tex]\[ 3/2 = 13/2 - 6c \][/tex]
Solving for [tex]\( c \)[/tex]:
[tex]\[ 3/2 = 13/2 - 6c \implies 6c = 13/2 - 3/2 \implies 6c = 10/2 \implies 6c = 5 \implies c = \frac{5}{6} \][/tex]
However, none of the given [tex]\( c \)[/tex] values (1 or 2) match [tex]\(\frac{5}{6}\)[/tex].
### Step 4: Check Given Options for [tex]\( c \)[/tex] and [tex]\( d \)[/tex]
The given options are:
1. [tex]\( c=1, d=3 \)[/tex]
2. [tex]\( c=1, d=9 \)[/tex]
3. [tex]\( c=2, d=8 \)[/tex]
4. [tex]\( c=2, d=9 \)[/tex]
Substituting these back into the equation and simplifying would show us if any simplify to True. Given an unsuccessful evaluation for matching coefficients and exponents, none of the provided options correctly satisfy the equation.
Thus, no values of [tex]\( c \)[/tex] and [tex]\( d \)[/tex] from the provided options make the given equation true.
[tex]\[ \sqrt{\frac{50 x^6 y^3}{9 x^8}} = \frac{5 y^6 \sqrt{2 y}}{d x} \][/tex]
true, we will simplify both sides of the equation and compare the expressions.
### Step 1: Simplify the Left Side
The left-hand side of the equation is:
[tex]\[ \sqrt{\frac{50 x^6 y^3}{9 x^8}} \][/tex]
Simplifying the expression inside the square root:
[tex]\[ \frac{50 x^6 y^3}{9 x^8} = \frac{50 y^3}{9 x^2} \][/tex]
Now apply the square root:
[tex]\[ \sqrt{\frac{50 y^3}{9 x^2}} = \frac{\sqrt{50 y^3}}{\sqrt{9 x^2}} \][/tex]
This can be further simplified to:
[tex]\[ \frac{\sqrt{50} \cdot \sqrt{y^3}}{3 x} = \frac{\sqrt{50} \cdot y^{3/2}}{3 x} \][/tex]
### Step 2: Simplify the Right Side
The right-hand side of the equation is:
[tex]\[ \frac{5 y^6 \sqrt{2 y}}{d x} \][/tex]
Simplifying the expression inside the numerator:
[tex]\[ 5 y^6 \sqrt{2 y} = 5 \cdot \sqrt{2} \cdot y^6 \cdot y^{1/2} = 5 \cdot \sqrt{2} \cdot y^{6 + 1/2} = 5 \cdot \sqrt{2} \cdot y^{13/2} \][/tex]
So, the right side becomes:
[tex]\[ \frac{5 \sqrt{2} y^{13/2}}{d x} \][/tex]
### Step 3: Equate the Simplified Forms
Equating the simplified left and right sides:
[tex]\[ \frac{\sqrt{50} \cdot y^{3/2}}{3 x} = \frac{5 \sqrt{2} \cdot y^{13/2}}{d x} \][/tex]
For the equation to be true, the powers of [tex]\( y \)[/tex] and [tex]\( x \)[/tex] must match on both sides, as well as the coefficients:
- The power of [tex]\( y \)[/tex] in [tex]\(\sqrt{50} \cdot y^{3/2}\)[/tex] is [tex]\( 3/2 \)[/tex].
- The power of [tex]\( y \)[/tex] in [tex]\( 5 \sqrt{2} \cdot y^{13/2}\)[/tex] is [tex]\( 13/2 \)[/tex].
This implies:
[tex]\[ 3/2 = 13/2 - 6c \][/tex]
Solving for [tex]\( c \)[/tex]:
[tex]\[ 3/2 = 13/2 - 6c \implies 6c = 13/2 - 3/2 \implies 6c = 10/2 \implies 6c = 5 \implies c = \frac{5}{6} \][/tex]
However, none of the given [tex]\( c \)[/tex] values (1 or 2) match [tex]\(\frac{5}{6}\)[/tex].
### Step 4: Check Given Options for [tex]\( c \)[/tex] and [tex]\( d \)[/tex]
The given options are:
1. [tex]\( c=1, d=3 \)[/tex]
2. [tex]\( c=1, d=9 \)[/tex]
3. [tex]\( c=2, d=8 \)[/tex]
4. [tex]\( c=2, d=9 \)[/tex]
Substituting these back into the equation and simplifying would show us if any simplify to True. Given an unsuccessful evaluation for matching coefficients and exponents, none of the provided options correctly satisfy the equation.
Thus, no values of [tex]\( c \)[/tex] and [tex]\( d \)[/tex] from the provided options make the given equation true.
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.